1991
DOI: 10.1002/art.1780340205
|View full text |Cite
|
Sign up to set email alerts
|

Synovial membrane histology and immunopathology in rheumatoid arthritis and osteoarthritis. In vivo effects of antirheumatic drugs

Abstract: We examined the histologic and immunopathologic features of the synovial membrane of 18 patients with rheumatoid arthritis (RA) and 12 patients with osteoarthritis (OA) who had undergone total knee arthroplasty. Patients were classified into 5 groups according to therapeutic regimen and disease: RA treated with nonsteroidal antiinflammatory drugs (NSAIDs), RA treated with NSAIDs and prednisone, RA treated with NSAIDs and methotrexate (MTX), OA treated with analgesics, and OA treated with NSAIDs. There were no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
92
0
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 155 publications
(100 citation statements)
references
References 35 publications
5
92
0
3
Order By: Relevance
“…It has been shown that the glucocorticoid sensitivity returns to normal after short-term treatment with methotrexate, which may explain its steroid-sparing properties. In accordance with observations made in patients with rheumatoid arthritis [16,17,28], the absence of a clear quantitative anti-inflammatory effect in severe asthma suggests that methotrexate exerts its effect by modulation of cell function rather than cell number.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…It has been shown that the glucocorticoid sensitivity returns to normal after short-term treatment with methotrexate, which may explain its steroid-sparing properties. In accordance with observations made in patients with rheumatoid arthritis [16,17,28], the absence of a clear quantitative anti-inflammatory effect in severe asthma suggests that methotrexate exerts its effect by modulation of cell function rather than cell number.…”
Section: Discussionsupporting
confidence: 83%
“…Similar observations have been made in synovia biopsies from patients with rheumatoid arthritis which have shown that MTX treatment induces an improvement in clinical and serological indices of disease activity but is not associated with a decrease in the inflammatory infiltrate in the synovia [28]. In addition, the density of the mononuclear cell infiltrate is higher in the synovial membranes from patients with rheumatoid arthritis treated with MTX when compared to the specimens from patients receiving nonsteroidal anti-inflammatory drugs with no differences being observed in the numbers of T-cell subsets or IL-2 bearing cells between the groups [28]. The authors also have been unable to show any differences in mast cell numbers, eosinophilia or the numbers of IL-4 and IL-5 positive cells in the biopsies of these patients before and after MTX treatment.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, reports from previous studies have raised the possibility that intraarticular glucocorticoid injections may even cause worsening of OA lesions by damaging cartilage (3-5). Previous studies at our laboratory (6) and others (7, 8) have indicated that in experimental OA, intraarticular injections of low-dose corticosteroids, such as triamcinolone hexacetonide, may reduce the progression of cartilage erosion and osteophyte formation. One of the goals of the present study was to examine whether another corticosteroid, methylprednisolone acetate, may also have a protective effect on OA lesions.…”
mentioning
confidence: 87%
“…In the present study, we have conducted a systematic characterization of gene expression in synovial tissues from affected joints of patients with RA and compared this expression with that in tissues from patients with osteoarthritis (OA), a degenerative joint disease characterized by progressive loss of cartilage, as a control (19)(20)(21)(22). Both diseases are complex clinical entities that share clinical and demographic characteristics, but they also harbor key differences in tissue destruction and prognosis.…”
mentioning
confidence: 99%